2008
DOI: 10.1167/iovs.07-1444
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Vessel Formation in the Choroid of Mice Lacking Tissue Inhibitor of Metalloprotease-3

Abstract: These findings suggest that the distinct choroidal phenotype in mice lacking TIMP3 may be the result of a local disruption of extracellular matrix and angiogenic homeostasis, and they support an important role of TIMP3 in the regulation of choroidal vascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 37 publications
2
50
1
Order By: Relevance
“…Furthermore, recent reports suggest that Timp3-deficient mice have kidney fibrosis. 31,42,43 We therefore investigated the microvasculature of normal Timp3 2/2 kidneys, the response of the kidney microvasculature to acute ischemia reperfusion injury (IRI), and the function of pericytes in these vascular responses. Adult Timp3 2/2 mice were smaller than littermate controls but had normal renal function and no albuminuria ( Table 2).…”
Section: Timp3 Mutant Mice Have a Kidney Microvascular Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent reports suggest that Timp3-deficient mice have kidney fibrosis. 31,42,43 We therefore investigated the microvasculature of normal Timp3 2/2 kidneys, the response of the kidney microvasculature to acute ischemia reperfusion injury (IRI), and the function of pericytes in these vascular responses. Adult Timp3 2/2 mice were smaller than littermate controls but had normal renal function and no albuminuria ( Table 2).…”
Section: Timp3 Mutant Mice Have a Kidney Microvascular Phenotypementioning
confidence: 99%
“…1,9,23 Timp3 2/2 gene-targeted homozygous mice and littermate controls were generated as previously described 31,43 and maintained on the C57BL6 background.…”
Section: Animalsmentioning
confidence: 99%
“…In humans, mutations in the TIMP-3 gene cause Sorsby's fundus dystrophy (Weber et al 1994), an autosomal dominant disorder characterized by abnormal Bruch's membrane thickening, choroidal neovascularization, retinal degeneration, and loss of vision usually by middle age (Sorsby and Mason 1949). Mice lacking TIMP-3 in their eyes develop abnormal choroidal vessels (Janssen et al 2008) The goal of this study was to characterize the distribution of TIMP-3 in human vascular tissues, using tissue microarrays (TMAs) containing samples taken from 100 subjects undergoing autopsy (Halushka et al in press). We hypothesized that TIMP-3 would be differentially expressed in the various tissues on these TMAs.…”
mentioning
confidence: 99%
“…In the eye TIMP-3 is closely related to Bruch's membrane and regulates angiogenesis (Janssen et al, 2008). Analysis of micromatrix demonstrated that out of investigated metalloproteinases and its inhibitors: MMP1, MMP2, MMP11, MMP14, MMP25, TIMP1, TIMP2, TIMP3 and TIMP4 which were present in pericytes, only TIMIP3 mRNA may play role in impairment of microcirculation in diabetic retinopathy (Barth et al, 2007).…”
Section: Tissue Inhibitor Of Matrix Metalloproteinase 3 (Timp-3)mentioning
confidence: 99%